2012
DOI: 10.1177/0022185612454974
|View full text |Cite
|
Sign up to set email alerts
|

Are Casual and Contract Terms of Employment Hazardous for Mental Health in Australia?

Abstract: The risk that flexible forms of employment are harmful to the health of workers is a major public health issue for the many countries, including Australia, where such forms of employment are common or have been growing. Casual, contract and part-time employment in Australia rose rapidly in the decade to 1998 and remains high at 40% of employees in 2011. We investigate the impacts on mental health of employment on these terms and of unemployment. We use nine waves of panel survey data and dynamic random-effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 29 publications
2
45
2
Order By: Relevance
“…In this Australian working population sample, poor mental health was not associated with employment arrangement, after adjustment for socio-demographic characteristics. This finding was consistent with a crosssectional study from a neighboring southeastern Australian state, Victoria [LaMontagne et al, 2012a], as well as findings from national longitudinal analyses [Llena-Nozal, 2009;Richardson et al, 2012]. Several international studies have also shown null findings, although the larger and prospective studies have tended to show an association Ferrie et al, 2008].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this Australian working population sample, poor mental health was not associated with employment arrangement, after adjustment for socio-demographic characteristics. This finding was consistent with a crosssectional study from a neighboring southeastern Australian state, Victoria [LaMontagne et al, 2012a], as well as findings from national longitudinal analyses [Llena-Nozal, 2009;Richardson et al, 2012]. Several international studies have also shown null findings, although the larger and prospective studies have tended to show an association Ferrie et al, 2008].…”
Section: Discussionsupporting
confidence: 87%
“…Only three very recent published studies (to our knowledge) have used Australian data to assess the association between casual employment arrangements and poor mental health. Neither of the two longitudinal studies showed an impact from entering casual employment, in contrast to most of the findings from other OECD countries [Llena-Nozal, 2009;Richardson et al, 2012], and this was corroborated by cross-sectional data from a survey in the state of Victoria [LaMontagne et al, 2012a]. The three studies used mental health summary scales derived from the SF-36 [Ware et al, 1994] or the more abbreviated SF-12 [Ware et al, 1996].…”
Section: Introductionmentioning
confidence: 96%
“…Changes in job stressors might also arise due to changes in labour force composition, which would be captured less efficiently by a cohort versus a repeat cross-sectional design 24. With respect to one important stratifying variable that could change substantially over time, employment arrangement, ABS cross-sectional labour force surveys indicate that the proportion of workers in casual employment permanent versus precarious employment arrangements has not changed substantially over the last decade 35. Offsetting these limitations, a strength of the cohort design and the population average modelling approach is that we were able to estimate average trends for population groups over time, taking into account the clustering of observations within individuals.…”
Section: Discussionmentioning
confidence: 99%
“…health can be both a predictor and an outcome of employment relations, with longitudinal studies needed to account for pre-existing health. (15) To our knowledge only two published longitudinal studies have explicitly examined the relationship between nonstandard employment and health in Australia, (16,17) and both suggested that entering casual employment was neither beneficial nor detrimental to workers' health. Notably, one of those studies was an international comparative analysis that found negative impacts in other OECD nations.…”
Section: Nonstandard Employment and Healthmentioning
confidence: 99%